Identification of Rv1133c (MetE) as a marker of Mycobacterium tuberculosis replication and as a highly immunogenic antigen with potential immunodiagnostic power - Iacobino, Angelo; Teloni, Raffaela; Mancone, Carmine; Facchiano, Francesco; Di Giamberardino, Alessandra; Senatore, Cinzia; Di Virgilio, Antonio; Lanni, Alessio; Giannoni, Federico; Nisini, Roberto; Mariotti, Sabrina (Frontiers in Immunology, 2024)
The immunization of mice with the sterile culture medium supernatants of Mycobacterium tuberculosis (Mtb) H37Rv permitted the production of several monoclonal antibodies (mAbs) specific for secreted and/or released antigens. Two mAbs bound and immunoprecipitated an 80 kDa protein that was identified by mass spectrometry as Rv1133c, the methionine synthase MetE. The protein MetE is ubiquitous among prokaryota and shows a significant sequence homology in many bacteria. We produced both the full-length recombinant MetE and its N-terminal fragment, whose sequence is more conserved among mycobacteria, to select mAbs recognizing a Mtb specific region of MetE. Finally, we produced and selected eight mAbs that specifically detect the MetE protein in the supernatant and cell lysate of Mtb and BCG, but not other bacteria such as non-tuberculous mycobacteria (NTM), Streptococcus pneumoniae, Staphylococcus aureus, Acinetobacter baumanii or E. coli. Taking advantage of our mAbs, we studied i) the vitamin B12 dependance for the synthesis of MetE in Mtb and NTM and ii) the kinetics of MetE production and secretion in supernatants during the in vitro reproduced replicative, dormant and resuscitation cycle of Mtb. Our data demonstrate that dormant Mtb, that are assumed prevalent in latent infections, as well as NTM do not produce and secrete MetE. Results indicate an unexpected specificity for Mtb of our anti-MetE mAbs and encourage the use of rMetE and our mAbs as tools for the immunodiagnosis of TB and its stages.